Does the Autophagy Related Gene 7 (ATG7) Have a Role in Non-Melanoma Skin Cancer? - Samaka RM; Basha MA; Mansour E (Dove Medical Press, 2020)
Rehab M Samaka, 1 Mohammed A Basha, 2 Eman Mansour 3 1Pathology Department, Faculty of Medicine, Menoufia University, Al Minufya, Egypt; 2Dermatology, Andrology and STDs Department, Faculty of Medicine, Menoufia University, Al Minufya, Egypt; 3Ministry of Health, El Menshawy General Hospital, Tanta, EgyptCorrespondence: Eman MansourMinistry of Health, El Menshawy General Hospital, Tanta, EgyptTel +201273906558Fax +20403305158Email htmsecti20@gmail.com Rehab M SamakaPathology Department, Faculty of Medicine, Menoufia University, Al Minufya, EgyptTel +201002806239Fax +20482317508Email Rehabsamaka@yahoo.comPurpose: To evaluate the role of autophagy related gene 7 (ATG7) in non-melanoma skin cancer.Subjects and Methods: This retrospective and prospective case-control study was performed on 104 patients with non-melanoma skin cancer (NMSC) in addition to 20 apparently healthy subjects matched for age and sex as a control group. Multiple skin biopsies were taken for immunohistochemical evaluation of ATG7 expression.Results: Both epithelial and stromal ATG7 were expressed in all participants while all patients showed nucleocytoplasmic localization and controls showed both cytoplasmic and nucleocytoplasmic expression. In addition, significantly higher H-scores of ATG7 in both epithelium and stroma were detected in patients compared to controls (P< 0.001).Conclusion: ATG7 nucleocytoplasmic topographic localization might be involved in the pathogenesis of NMSC, which can open the gate for new target therapy for this skin cancer.Keywords: autophagy, autophagy related gene 7, BCC, SCC, NMSC